2011
DOI: 10.1037/a0025879
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual stress and coping model of divorce: A longitudinal study.

Abstract: This study represents the first longitudinal effort to use a spiritual stress and coping model to predict adults' psychosocial adjustment following divorce. A community sample of 89 participants completed measures at the time of their divorce and 1 year later. Though the sample endorsed slightly lower levels of religiosity than the general U.S. population, most reported spiritual appraisals and positive and negative religious coping tied to divorce. Hierarchical regression analyses controlling general religiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 61 publications
2
36
0
3
Order By: Relevance
“…Terms & who divorce, as compared with individuals who are married (Amato, 2000;Hughes & Waite, 2009). Research supported that spousal infidelity (Blow & Harnett, 2005;Ortman, 2005), initiator status (Locker, McIntosh, Hackney, Wilson, & Wiegand, 2010;Sweeny & Horwitz, 2001), and spiritual well-being (Krumrei, Mahoney, & Pargament, 2011;Steiner, Suarez, Sells, & Wykes, 2011) can affect how an individual adjusts to divorce. Divorce-related research conducted to understand how men versus women adjust has shown that the effects on mental health for either gender have appeared to be comparable (Amato, 2010).…”
Section: Effect Of Infidelity Initiator Status and Spiritual Well-bmentioning
confidence: 94%
See 2 more Smart Citations
“…Terms & who divorce, as compared with individuals who are married (Amato, 2000;Hughes & Waite, 2009). Research supported that spousal infidelity (Blow & Harnett, 2005;Ortman, 2005), initiator status (Locker, McIntosh, Hackney, Wilson, & Wiegand, 2010;Sweeny & Horwitz, 2001), and spiritual well-being (Krumrei, Mahoney, & Pargament, 2011;Steiner, Suarez, Sells, & Wykes, 2011) can affect how an individual adjusts to divorce. Divorce-related research conducted to understand how men versus women adjust has shown that the effects on mental health for either gender have appeared to be comparable (Amato, 2010).…”
Section: Effect Of Infidelity Initiator Status and Spiritual Well-bmentioning
confidence: 94%
“…The activities associated with positive spiritual coping are varied, such as (a) seeking control or relief by working together with God to manage the divorce; (b) engaging in prayer, private rituals, or public worship to overcome negative feelings; (c) seeking spiritual purification for wrongdoings that contributed to the divorce; and (d) searching for comfort through the love, care, or spiritual intimacy with congregation members, clergy, or both. Furthermore, divorced people might develop negative spiritual coping (viewing the divorce as a punishment from God and tension within one's own religious community), which might lead to more difficulties in adjusting to the divorce and a higher level of depression (Krumrei et al, 2011). Depending on how a person views divorce in the context of their religious beliefs, positive spiritual or religious coping can help the individual to overcome the negative effects of divorce.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Tal fato pode ter ocorrido em decorrência da utilização de apenas um único item (Gouveia et al, 2009), semelhante ao empregado na presente pesquisa. Entretanto, era esperado que as pessoas com maior nível de religiosidade seriam mais propensas a concederem o perdão, tendo em vista sua crença no casamento como algo sagrado e sua dissolução como um ato de desrespeito a ordem divina (Krumrei, Mahoney, & Pargament, 2011).…”
Section: Discussionunclassified
“…This may be a result of using only a single item (Gouveia et al, 2009), similar to that employed in the present study. However, it was expected that people with higher levels of religiosity would be more likely to grant forgiveness, considering they believe that marriage is sacred and its dissolution is an act of disrespect toward divine order (Krumrei, Mahoney, & Pargament, 2011).…”
Section: Discussionmentioning
confidence: 99%